1994
DOI: 10.1177/105268469400400104
|View full text |Cite
|
Sign up to set email alerts
|

Principals who Empower Teachers

Abstract: Efforts to restructure schools typically include broadening decisionmaking arenas to include teacher input. Principals, however, have not been prepared to share leadership roles with their faculties, nor have researchers examined the characteristics of principals who are willing and able to empower teachers. Leader authenticity has been associated with more open climates in schools. In this study, the authors examined the relationship between principal authenticity and faculty empowerment in 30 high schools. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…However, effects on empowerment were only briefly alluded to in terms of greater classroom freedom, collective sense of ownership, more discussion, and critique of practice. Kirby and Colbert (1992) found that principal authenticity (i.e., putting self over role, nonmanipulation of subordinates, accountability) was significantly related to one aspect of teacher empowerment described by Maeroff (1988)-access to knowledge (i.e., ability of teachers to acquire information) and skills about shared decision making.…”
mentioning
confidence: 96%
“…However, effects on empowerment were only briefly alluded to in terms of greater classroom freedom, collective sense of ownership, more discussion, and critique of practice. Kirby and Colbert (1992) found that principal authenticity (i.e., putting self over role, nonmanipulation of subordinates, accountability) was significantly related to one aspect of teacher empowerment described by Maeroff (1988)-access to knowledge (i.e., ability of teachers to acquire information) and skills about shared decision making.…”
mentioning
confidence: 96%
“…Research dealing with leadership style and job satisfaction has indicated that there is a need to examine principals' behaviors in establishing the schools' working conditions that impact the level of overall teacher job satisfaction. The findings of this study supported that need among those that train future administrators and create educational policy (Kirby & Colbert, 1994;Thompson, 1992;Tucker & Mandel, 1986Murphy, 1988. Implications for universities and agencies who train future administrators, create policy for education, or provide staff development for those administrators are present.…”
Section: Discussionsupporting
confidence: 61%
“…Holland commented, "Some teachers don't want to bother to change their teaching methods late in their careers; others have seen so many educational trends come and go that they're not about to embrace change without a lot of convincing" (p. 6). School reform literature (Holland, 1998;Sexton, 1992;Whitener, 1997) (Sexton, 1992;Smith, 1994 Kirby and Colbert (1994) have emphasized that administrator preparation programs have been criticized for their focus on managerial tasks.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…First, they empowered themselves on the basis of their experience and the trust shown in them by the school principal in SBCD. According to Kirby and Colbert (1992), experience and the trust of one's peers and superiors are fundamental to teachers' empowerment. In School L, teachers' experience in teaching, their professional qualifications, and their permanent contracts all contributed to teachers' empowerment in SBCD.…”
Section: Democratic School Environment: Increased Motivation and Indementioning
confidence: 99%